Early responses of human periodontal ligament fibroblasts to cyclic and static mechanical stretching. (8th December 2016) - Papadopoulou, Adamantia; Iliadi, Anna; Eliades, Theodore; Kletsas, Dimitris
Summary: Objective: To compare the mechanotransduction caused by cyclic and static mechanical strains in human periodontal ligament fibroblasts (hPDLFs) cultured under identical conditions. Materials and methods: hPDLFs, originating from the same donors, were exposed either to cyclic or to static tensile strain using specially designed devices and under identical culture conditions. Activation of all members of mitogen-activated protein kinases (MAPKs) was monitored by western immunoblot analysis. Expression levels of immediate/early genes c-fos and c-jun were assessed with quantitative real-time polymerase chain reaction. Results: Time course experiments revealed that both types of stresses activate the three members of MAPK, that is ERK, p38, and JNK, with cyclic stress exhibiting a slightly more extended activation. Further downstream, both stresses upregulate the immediate/early genes c-fos and c-jun, encoding components of the activator protein-1 (AP-1), a key transcription factor in osteoblastic differentiation; again cyclic strain provokes a more intense upregulation. Six hours after the application of both strains, MAPK activation and gene expression return to basal levels. Finally, cells exposed to cyclic stress for longer periods are distributed approximately perpendicular to the axis of the applied strain, whereas cells exposed to static loading remain in a random orientation in culture. Conclusion: The findings of the present study indicate similar, although not identical, immediate/early responses of hPDLs to cyclic and static stretching, with cyclic strain provoking a more intense adaptive response of these cells to mechanical deformation.